MENGANALISIS TEOLOGI PASTORAL DALAM MEMBENTUK SEMANGAT KEPEMIMPINAN KRISTEN PADA ERA POSTMODERN: TINJAUAN YESAYA 40:1 - Alvrianti Palallang; Oktovianus P. (ADISAM PUBLISHER, 2023)
This research aims to analyze the role of pastoral theology in shaping Christian leadership spirit in the postmodern era, with a focus on the observation of Isaiah 40:1. The postmodern era is characterized by a shift in societal values and worldviews, influencing how Christian leadership can guide and motivate their communities. Isaiah 40:1 provides a rich theological context of comfort and restoration, which can serve as a source of inspiration for Christian leaders to develop relevant and effective leadership spirit amidst the challenges of the postmodern era. The research methodology involves the analysis of the text of Isaiah 40:1 within the context of pastoral theology, employing a holistic hermeneutical approach to grasp the overall message of the text. Additionally, a comparative study of pastoral theology and contemporary Christian leadership literature is conducted to identify principles that can be adopted and applied in the context of the postmodern era. The anticipated outcome of this research is to provide profound insights into how pastoral theology, particularly in the context of Isaiah 40:1, can shape a Christian leadership spirit that is responsive to the changes and challenges in postmodern society. The practical implications of this research include the development of resources and strategies to assist Christian leaders in guiding and motivating their communities in a manner that is both adequate and relevant in the current era.